A membrane-based flat-plate liquid desiccant dehumidification air-conditioning system - Bai, Hongyu (2019)
The enormous increase of energy consumption for building indoor environment, specifically for indoor thermal comfort has brought numerous state-of-art technologies as alternatives to the traditional vapour compression air-conditioning system. The membrane-based liquid desiccant dehumidification has gain wide attention for good feasibility, high energy efficiency and no desiccant carry-over problem. As a matter of fact, the membrane-based liquid desiccant system is still under research and development stage with limited number of literatures.